The Role of Separator Thermal Stability in Safety Characteristics of Lithium-ion Batteries. Issue 9 (1st September 2022) - Zhou, Hanwei; Fear, Conner; Parekh, Mihit; Gray, Frederick; Fleetwood, James; Adams, Thomas; Tomar, Vikas; Pol, Vilas G.; Mukherjee, Partha P.
Abstract : The thermal instability of polymer separators severely threatens the safety characteristics of lithium-ion (Li-ion) batteries. Separators will melt, shrink, vaporize, and collapse under high temperatures, leading to internal short circuits and thermal runaway catastrophes of the cell. Therefore, the amelioration of battery safety challenges benefits from a fundamental understanding of separator behaviors under thermally abusive scenarios. This work investigates the role of separator thermal stability in modulating Li-ion cell safety performance. Three types of separators made of commercially available cellulose, trilayer polypropylene/polyethylene/polypropylene, standard polypropylene, and an in-house modified graphene-polydopamine coated separator are fabricated in custom single layer pouch cells and subjected to accelerating rate calorimeter (ARC) tests to investigate dynamic thermo-electrochemical interactions. The safety hazards of 18650 cylindrical cells assembled with different types of separators are predicted using a verified ARC computational model to compare the effects of separator heat resistance on cell-level thermal runaway risks. This study reveals the thermally robust mechanisms of diverse separator microstructures, indicating how the in-house modified graphene-polydopamine coated separator significantly enhances the safety limits of Li-ion batteries.